Socio-demographic profile of multi-drug resistant tuberculosis patients and its association with severity of adverse drug reactions in DOTS plus centre at tertiary hospital in Himachal Pradesh, India - Kumari, Anita; Sharma, Parveen K.; Kansal, Dinesh; Bansal, Rekha; Kumari, Sumita (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Multi-drug resistant tuberculosis has become major public health problem and obstacle to effective control of tuberculosis. Objectives was to study the socio-demographic profile of multi- drug resistant tuberculosis patients and its association with severity of ADR (adverse drug reactions) in DOTS plus centre at tertiary hospital in Himachal Pradesh. Methods: It was a prospective observational study carried out from November 2012 to October 2013 on multi-drug resistant tuberculosis (MDR-TB) patients after approved from Institutional Ethics Committee. Results: Out of 104 patients the mean age of patients was 39.9 ±14.26 years. Majority of the patients were in the economically productive age groups. Multi-drug resistant tuberculosis was more in male (76%) than female (24%) and 96% of patients were belonged to rural area. The educational status of the MDR-TB shows 24% patients were illiterate. 63.46% MDR-TB patients were underweight (BMI<18.5%) according to WHO guidelines for obesity. Severity of ADR assessed by Hart wig and Siegel’s scale showed 21% patients experienced mild ADRs, 49% patients had moderate and 17% patients had severe ADRs. Severity of ADR is seen more in male, economically productive age group, subjects on vegetarian diet, patients who were underweight (BMI<18.5%) and with lower educational status. Conclusions: MDR-TB is a rapidly increasing health problem with major socio-economic and individual consequences. Multi-drug resistant tuberculosis mainly affects middle age that is in the economically productive age group which hampers the social and economic development of individual, society and nation.